Private military companies : peace or profit? : A comparative analysis of private military involvement in Africa and the Middle East - Steenekamp, Cindy Lee (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- University of Stellenbosch, 2006.